New markers for regulation of transcription and macromolecule metabolic process in porcine oocytes during in vitro maturation - Brązert, Maciej; Kranc, Wiesława; Nawrocki, Mariusz J; Sujka-Kordowska, Patrycja; Konwerska, Aneta; Jankowski, Maurycy; Kocherova, Ievgeniia; Celichowski, Piotr; Jeseta, Michal; Ożegowska, Katarzyna; Antosik, Paweł; Bukowska, Dorota; et al. (Molecular medicine reports, 2020)
Oocyte maturation is essential for proper fertilization, embryo implantation and early development. While the physiological conditions of these processes are relatively well‑known, its exact molecular mechanisms remain widely undiscovered. Oocyte growth, differentiation and maturation are therefore the subject of scientific debate. Precious literature has indicated that the oocyte itself serves a regulatory role in the mechanisms underlying these processes. Hence, the present study performed expression microarrays to analyze the complete transcriptome of porcine oocytes during their in vitro maturation (IVM). Pig material was used for experimentation, as it possesses similarities to the reproductive processes and general genetic proximities of Sus scrofa to human. Oocytes, isolated from the ovaries of slaughtered animals were assessed via the Brilliant Cresyl Blue test and directed to IVM. A number of oocytes were left to be analyzed as the 'before IVM' group. Oocyte mRNA was isolated and used for microarray analysis, which was subsequently validated via RT‑qPCR. The current study particularly focused on genes belonging to 'positive regulation of transcription, DNA‑dependent', 'positive regulation of gene expression', 'positive regulation of macromolecule metabolic process' and 'positive regulation of transcription from RNA polymerase II promoter' ontologies. FOS, VEGFA, ESR1, AR, CCND2, EGR2, ENDRA, GJA1, INHBA, IHH, INSR, APP, WWTR1, SMARCA1, NFAT5, SMAD4, MAP3K1, EGR1, RORA, ECE1, NR5A1, KIT, IKZF2, MEF2C, SH3D19, MITF and PSMB4 were all determined to be significantly altered (fold change, >|2|; P<0.05) among these groups, with their downregulation being observed after IVM. Genes with the most altered expressions were analyzed and considered to be potential markers of maturation associated with transcription regulation and macromolecule metabolism process.
Keywords: Animals; ovarium; Female; Oogenesis; biologické markery; Biomarkers; Gene Expression Regulation, Developmental; oogeneze; ženské pohlaví; genové regulační sítě; Oocytes; Transcription, Genetic; energetický metabolismus; Immunohistochemistry; buněčná diferenciace; rna; oocyty; prasata; Energy Metabolism; Metabolomics; Gene Regulatory Networks; stanovení celkové genové exprese; kultivované buňky; imunohistochemie; metabolomika; genetická transkripce; Cells, Cultured; Computational Biology; Swine; transcription; pig; transkriptom; Cell Differentiation; zvířata; oocyte; Transcriptome; vývojová regulace genové exprese; výpočetní biologie; in vitro maturation; Gene Expression Profiling; Ovary